A study on the impact of mental health problems on the academic buoyancy of medical students and the mechanisms - Hu, Bin; Wang, Yue; Zhou, Hai Tao; Li, Min; Zheng, Li (Frontiers in Public Health, 2024)
Objective To analyze the effects of different family environmental backgrounds and mental health problems on academic buoyancy and to explore the potential mechanisms of their effects, using a sample of 2085 medical students in Jiangsu province. Methods Using the multiple linear regression to analyze the impact of mental health problems on academic buoyancy in different family environment contexts. Results (1) Higher family income and parental literacy implied higher levels of academic buoyancy in children; (2) mental health problems and academic buoyancy were negatively related, and generalized anxiety and uncertainty stress negatively predicted academic buoyancy levels; (3) uncertainty stress may have an indirect effect on academic buoyancy levels through a partially mediating effect of generalized anxiety.